Evaluation of Herbicides for Enhancing Yield and Economic Benefits in Barley (Hordeum vulgare L.) - Singh, Gurudev; Chopra, Pankaj; Manuja, Sandeep; Kaur, Navneet; Singh, Gurpreet (International Journal of Bio-resource and Stress Management, 2025)
The research experiment was conducted during November, 2014–May, 2015, November, 2015–May, 2016 and November, 2016–May, 2017 at two locations (HAREC-Bajaura, Kullu and RWRC-Malan, Kangra) in Himachal Pradesh to evaluate different herbicides for effective weed control in barley. This experiment consisting of eleven treatments viz. Pinoxoden 30, 40 and 50 g ha-1, pinoxoden 40 g ha-1+metsulfuron 4 g ha-1 , pinoxoden 40 g ha-1 fb. metsulfuron 4 g ha-1, pinoxoden 40 g ha-1+carfentrazone 20 g ha-1, isoproturon 1000 g ha-1, isoproturon 750 g ha-1+2, 4-D 500 g ha-1, isoproturon 750 g ha-1+metsulfuron 4 g ha-1, weedy and weed free check was conducted in RBD with 3 replications. The results revealed that on pooled basis, at both locations, isoproturon 750 g ha-1+metsulfuron 4 g ha-1 being at par with pinoxoden 40 g ha-1+metsulfuron 4 g ha-1 and pinoxoden 40 g ha-1 fb. metsulfuron 4 g ha-1 resulted in significantly higher barley grain yield, which was equivalent to weed free check. Due to higher yield obtained in plots receiving application of isoproturon 750 g ha-1+metsulfuron 4 g ha-1 at Bajaura and pinoxoden 40 g ha-1+metsulfuron 4 g ha-1 at Malan, had fetched highest net returns and BC ratio. In on-farm trials, where three prominent treatments were tested at different locations of H.P., isoproturon 750 g ha-1+metsulfuron 4 g ha-1 had achieved highest average grain yield of barley.